Rechallenge capecitabine after fluoropyrimidine-induced cardiotoxicity in rectal cancer: A case report. Issue 2 (January 2019) - Peng, Tao; Ouyang, Yulu; Tong, Kanger
Abstract: Rationale: Fluoropyrimidine-induced cardiotoxicity is a rare but potentially serious toxicity. The most common symptom is anginal chest pain. Patient concerns: A 35-year-old woman was diagnosed with rectal cancer with metastasis to the liver. Diagnosis: A computed tomography scan showed a 9.3 × 4.5-cm predominantly hypodense lesion within the left lobe of the liver and thickening of the rectum. Liver biopsy showed moderately differentiated adenocarcinoma with necrosis involving the liver parenchyma, and immunohistochemistry for mismatch repair proteins indicated that the tumor was positive for MutL Homolog 1, MutS Homolog 2, MutS Homolog 6, and Protein Homolog 2. Rectal biopsy indicated moderately differentiated adenocarcinoma. Interventions: She received chemotherapy of fluorouracil 1600 mg/m 2, leucovorin 500 mg/m 2, and irinotecan 100 mg/m 2 every week. During the second cycle of chemotherapy, she developed severe anginal chest pain. We replaced fluorouracil with capecitabine 1500 mg (3 pills) a day every 2 weeks, with 1 week off, with irinotecan 100 mg/m 2 on day 1 and bevacizumab 5 mg/kg at 200 ml/h for 30 min every 2 weeks. She was treated with chemotherapy for approximately 6 months. Outcomes: The liver lesion showed a significant response to chemotherapy, so she underwent resection of the liver tumor and rectum. After the surgery, she received radiation therapy to the rectal area, and 3 months of chemotherapy were administered prior to colostomy reversal. Lessons: Although the mechanism of fluoropyrimidine-induced cardiotoxicity is still uncertain, our case provides clinical evidence that cardiotoxicity could be a dose-related complication. Reducing the dose of fluoropyrimidine should be considered as a strategy after fluoropyrimidine-induced cardiotoxicity. However, this must be discussed with a multidisciplinary team including oncologists and cardiologists. Close monitoring of serial biomarkers and echocardiography are necessary for early diagnosis of cardiotoxicity.